2016
DOI: 10.4172/2375-4494.1000314
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Self-rated Psychopathic Traits and Psychopathology in a Sample of Finnish Community Youth: Exploration of Gender Differences

Abstract: Background: Associations between psychopathic traits and other forms of psychopathology among youth in the community, as well as gender differences in these associations have been scarcely studied yet. The present study aimed to explore this relationship in a sample of Finnish mid-adolescent girls and boys. Methods:The sample comprised 370 secondary school ninth-graders with the mean age of 15.1 years (SD 0.28). The Youth Psychopathic traits Inventory (YPI) and the Youth Self Report (YSR) served as self-assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…An extensive body of research has documented that a high proportion of especially youths from the high-risk sample meet criteria for psychopathology [ 22 , 23 ]. Since psychopathic traits have been found to be related to psychopathology (e.g., [ 8 , 9 , 21 ]) and psychopathology has been found to be related to delinquent behavior in youths (e.g., [ 22 24 ]), it is reasonable to suggest that the level of psychopathology influences the relationship between psychopathic traits and specific forms of delinquent behavior, and therefore may have influenced our results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An extensive body of research has documented that a high proportion of especially youths from the high-risk sample meet criteria for psychopathology [ 22 , 23 ]. Since psychopathic traits have been found to be related to psychopathology (e.g., [ 8 , 9 , 21 ]) and psychopathology has been found to be related to delinquent behavior in youths (e.g., [ 22 24 ]), it is reasonable to suggest that the level of psychopathology influences the relationship between psychopathic traits and specific forms of delinquent behavior, and therefore may have influenced our results.…”
Section: Discussionmentioning
confidence: 97%
“…The few studies focusing on psychopathic traits in non-juvenile justice youths demonstrate that psychopathic traits are highly associated with delinquent behavior. For example, Oshukova et al [ 8 ] found that in a community sample, in both boys and girls, psychopathic traits were highly correlated with rule-breaking and aggressive behavior. In addition, the correlation between psychopathic traits and rule-breaking behavior was significantly higher in boys than in girls.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that adolescent girls express better self-observation readiness than boys. For example, studies using the Youth Self-Report (YSR) instrument by Achenbach and Rescorla [ 37 ] have repeatedly found that girls report more problems in their emotional and behavioral functioning than boys [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%